If you take a mouse to school - Numeroff, Laura Joffe; Bond, Felicia (New York : Laura Geringer Books, 2002)
Describes the mountain of mischief a mouse could get into--in science class, reading class, and playtime, for example--if he came along to school.
School Library Journal, September 2002.
Book Links (A.L.A.), November 2005.
Publisher's Weekly, June 2002.
Horn Book, April 2003.
Bulletin (Center for Children's books), October 2002.
Kirkus Review, June 2002.
Keywords: Schools -- Fiction; Mice -- Fiction; School stories; Animal fiction